Analisis Performa Keuangan Perusahan pada PT Indofood Sukses Makmur, Tbk Periode 2018-2023 - Dewi Ambarwati; Dhea Anggraini; Permata Dian Pratiwi (Economic Reviews Journal, 2024)
This research is analyzing financial performance of PT Indofood Sukses Makmur, Tbk from 2018-2023 using liquidity, probability, solvency and activity. The objective of this study is to assess the company's ability to overcome challenges, particularly during the COVID-19 pandemic, and to understand the strategies it implemented in response. Data for this research was sourced from financial reports on the Indonesia Stock Exchange and analyzed using a quantitative descriptive approach. The study finds that the liquidity ratios show a positive trend, with an average Current Ratio of 145.9% and a Quick Ratio of 104.7%, indicating the company's strong capacity to meet short-term liabilities. Profitability remains stable, with an average Return on Investment (ROI) of 6.3% and Return on Equity (ROE) of 12.1%, reflecting the company's efficiency in generating profits. The solvency analysis, based on the Debt to Asset Ratio (DAR) averaging 48.2%, shows a balanced level of debt, while the decreasing Debt to Equity Ratio (DER) suggests improved debt management. The activity ratios, including Total Asset Turnover (TAT) and Fixed Asset Turnover (FAT), highlight consistent efficiency in utilizing assets to drive revenue. Despite the challenges posed by the pandemic, PT Indofood Sukses Makmur, Tbk has maintained solid financial health, demonstrating robust liquidity, stable profitability, and effective solvency and asset management. This research aims to contribute to financial literature and serve as a reference for both companies and investors in making informed strategic decisions.